Notes on the Carpophilus Stephens (Coleoptera: Nitidulidae) of Australia, with a new species from Victoria - Powell, Gareth S.; Hamilton, Maiya L. (Zootaxa, 2019)
A new species of the genus Carpophilus Stephens is described from Australia. This species is currently placed in the subgenus Myothorax Murray, although the group is in need of formal revision. A diagnosis is given to distinguish the new species from all other species of Myothorax in Australia. Additionally, a discussion of type material from Carpophilus described by MacLeay is added with formal lectotype designations for Carpophilus aterrimus MacLeay and Carpophilus pilipennis MacLeay. Taxonomic notes are also given for Carpophilus aterrimus MacLeay, while Carpophilus planatus Murray is removed from synonymy and treated as a valid taxon.